Toxic supervision, dehumanisation and SMEs performance in Nigeria: Moderating role of resilience - Ojeleye, Yinka Calvin; Ojeleye, Chioma Ifeoma (Oeconomica Jadertina, 2024)
This quantitative research explores the moderating role of resilience in the relationship between toxic supervision, dehumanisation, and the performance of small and medium-sized enterprises (SMEs) in Zamfara State. Using a survey and cross-sectional research technique, data were obtained from 658 employees of SMEs in Zamfara state, Nigeria. The research increased the sample size by 30% to account for any non-response error, ensuring that the analysis was robust. Using Structural Equation Modelling (SEM), the data demonstrate strong direct and moderating effects. First, toxic supervision has a negative influence on SME performance, underscoring the critical role of leadership behaviour. Furthermore, dehumanisation was shown to have a considerable negative effect on SME performance, highlighting the need to preserve humane treatment in the workplace. Notably, resilience appeared as an important moderator, buffering the negative impacts of toxic supervision and dehumanisation on SME performance. The study underscores the importance of building employees’ resilience in the workplace to act as buffer of the negative work trends like dehumanisation and toxic supervision by management of organisations. The model accounted for 42.8% of the variation in SME performance, demonstrating moderate explanatory power, and had a Q-Square value of 0.155, indicating medium predictive significance. This research adds to our knowledge of organisational behaviour in SMEs by providing insights into techniques for building resilience and improving performance in difficult working situations.
Keywords: toxic supervision; Dehumanisation; SMEs performance; Resilience; Social exchange theory